Comparative Risks of High-Grade Adverse Events Among FDA-Approved Systemic Therapies in Advanced Melanoma: Systematic Review and Network Meta-Analysis - Huang, Ya-fang; Xie, Wen-jie; Fan, Hai-yu; Du, Juan (Frontiers in Oncology, 2020)
Background: Head-to-head evidence is lacking in comparative risks of high-grade adverse events (AEs) among different systemic treatment options for advanced melanoma. Methods: An up-to-date systematic review and network meta-analysis (NMA) was performed. Randomized controlled trials (RCTs) of patients with advanced melanoma were eligible if at least one intervention was the Food and Drug Administration–approved targeted or immune checkpoint inhibitors. Risks of high-grade AEs were estimated by random-effects Bayesian NMAs, based on relative risks. Surface under the cumulative ranking probabilities was used to assess relative ranking of treatments. The summary incidences were calculated. Results: Twenty-five RCTs (12,925 patients) comparing 10 different systemic treatment options were included. BRAF/MEK had the highest risk of overall high-grade AEs (pooled incidence: 32.11%). BRAF had the highest risk of high-grade arthralgia (0.39%), whereas MEK had the highest risk of high-grade hypertension (2.28%) and nausea (0.37%). Cytotoxic T-lymphocyte antigen 4 (CTLA-4)/chemo had the highest risk of high-grade diarrhea (1.31%), alanine aminotransferase (0.60%), and aspartate aminotransferase elevation (0.59%). Programmed cell death 1 (PD-1)/CTLA-4 had the highest risks of high-grade pyrexia (1.14%) and rash (0.94%). Using PD-1 inhibitor alone had the lowest risks of overall high-grade AEs. Conclusions: Different systemic treatment options have varying high-grade AEs in advanced melanoma treatment. Current evidences highlight the important risks of BRAF/MEK, CTLA-4/chemo, and PD-1/CTLA-4.